Conflict in Africa : concepts and realities - Bozeman, Adda B. (Adda Bruemmer), 1908-1994 (Princeton legacy library., 1976)
Do modern Western ideas about the nature of conflict and its resolution apply to Africa? To answer this question, Adda Bozeman examines conflict in Africa south of the Sahara in its many social, political, and cultural aspects, past and present. The author shows how African perspectives on war and diplomacy have evolved under the influence of nonliteracy, tribalism, and a concept of undifferentiated time. In addition, she confirms that indigenous cultural traditions are resurgent everywhere, making it unlikely that African political values will become more closely aligned with those of the West. The two civilizations view conflict differently and have different ways of resolving it. The Africans are more at ease with conflict than their Western counterparts, and they do not see war and peace as the mutually exclusive phenomena that Occidental societies hold them to be. The author concludes that modern Western concepts of conflict not only do not, but cannot, allow for African realities. Originally published in 1976. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.